A study of removal of precipitated iron in water using filtration - Mohd Afiq Bin Harun, Mohd Afiq (2009)
A research were made to study the feasibility using sand in filtration pilot plant and also evaluate its performance to remove precipitate iron from water by using filtration. The pilot plant consists of a column packed with filter media, a transfer pump, sump tank, a rotameter, a bank of manometer tubes and various valves for flow control and sampling point.